تفسیرہدایت القرآن از سعید احمد پالنپوری میں قرآن پر کفارو مشرکین کےاعتراضات کے جوابات کا تجزیاتی مطالعہ: An Analytical Study of the Responses to Disbelievers’ Objections on the Qur’ān in Tafsīr Hidāyat al-Qurʾān by Saʿīd Aḥmad Pālanpūrī (Al-Aasar, 2025)
This research article explores how Tafsīr Hidāyat al-Qurʾān, a significant exegetical work by the renowned scholar Mufti Saʿīd Aḥmad Pālanpūrī, addresses the objections raised by disbelievers (kuffār and mushrikīn) against the Qur’ān. Mufti Pālanpūrī, a towering personality in the world of Islamic scholarship and the former Shaykh al-Ḥadīth at Dār al-ʿUlūm Deoband, played a monumental role in completing and expanding upon the initial work of ʿUthmān Kāshif al-Hāshimī in this exegesis. The tafsīr is widely recognized for its focus on aḥkām, Qur’ānic narratives, and its strong rational and spiritual appeal.This paper identifies and analytically discusses key objections historically raised by the polytheists of Makkah, particularly concerning the divine nature of the Qur’ān. These include doubts about the authenticity of revelation, accusations against the Prophet ﷺ, and challenges to the linguistic and literary uniqueness of the Qur’ān. Mufti Pālanpūrī refutes these objections with deep linguistic insight, powerful theological reasoning, and references to the Qur’ān’s inimitability (iʿjāz al-Qurʾān). The study concludes that Hidāyat al-Qurʾān successfully defends the divine authorship of the Qur’ān by demonstrating its unmatched eloquence, rhetorical coherence, and logical depth, making it impossible for human beings to replicate even a single verse. The tafsīr reaffirms that the Qur’ān's miraculous nature is a standing challenge to all humankind, validating its status as the unalterable word of God.